SDGS in children during the COVID-19 pandemic in Indonesia - Aman B Pulungan (Indonesian Nutrition Association, 2020)
This global pandemic negatively affects many aspects of children and adolescent health in Indonesia, including our journey in achieving SDGs. Even before the pandemic, our country is not yet on the right track in our SDGs journey with no national comprehensive programs. If we do not urgently address the problems in our nation’s health system, the COVID-19 pandemic can be detrimental to our SDGs progress.